Garnet microstructures suggest ultra-fast decompression of ultrahigh-pressure rocks - Luisier, Cindy; Tajcmanová, Lucie; Yamato, Philippe; Duretz, Thibault (Nature Communications, 2023)
Plate tectonics is a key driver of many natural phenomena occurring on Earth, such as mountain building, climate evolution and natural disasters. How plate tectonics has evolved through time is still one of the fundamental questions in Earth sciences. Natural microstructures observed in exhumed ultrahigh-pressure rocks formed during continental collision provide crucial insights into tectonic processes in the Earth’s interior. Here, we show that radial cracks around SiO2 inclusions in ultrahigh-pressure garnets are caused by ultrafast decompression. Decompression rates of at least 8 GPa/Myr are inferred independently of current petrochronological estimates by using thermo-mechanical numerical modeling. Our results question the traditional interpretation of fast and significant vertical displacement of ultrahigh-pressure tectonic units during exhumation. Instead, we propose that such substantial decompression rates are related to abrupt changes in the stress state of the lithosphere independently of the spatial displacement.